Avian Retrovirus‐Mediated Tumor‐Specific Gene Knockout. Issue 1 (16th January 2018) - Wang, Wei; Dong, Bingning; Yang, Feng
Abstract: The RCAS (replication‐competent avian sarcoma leukosis virus long‐terminal repeat with splice acceptor)‐TVA (tumor virus A) gene delivery system has been successfully used in modeling human cancers. Based on this, we have recently developed a novel RCI‐Oncogene (RCAS‐Cre‐IRES‐Oncogene) gene delivery system that can be used to efficiently manipulate gene expression in spontaneous tumors in vivo. We used this system for tumor gene knockout (TuKO) and demonstrated a crucial role of FGFR1 in driving mammary tumor metastasis. This versatile tumor gene modification system can also be adapted into different configurations to address different questions in appropriate mutant mouse hosts. Here we describe a protocol using the TuKO approach to knock out a gene of interest in tumors in appropriate hosts. © 2018 by John Wiley & Sons, Inc.